Optimization of polyhydroxybutyrate fermentation in shake flasks using oil palm trunk sap medium and scale up to 20 liter stirred tank fermenter - Syaza Afifah, Rosley (2014)
The uses of synthetic plastic nowadays giving many bad effects to the environment. Inabilities of synthetic plastic to degrade completely and took hundreds years to degrade entirely make a problem especially to the mother nature. To overcome these problems, the researcher were came with the idea to form a biodegradable plastic to replace the existing plastic that can produce microbially and using a renewable source which was polyhydroxybutyrate (PHB). However, PHB have a problem to produce in a large scale because need a higher cost compared to the petrochemical based plastic. The carbon source for the PHB is expensive than the synthetic plastic. In this study Oil Palm Trunk Sap (OPTS) were used as the carbon source of the fermentation of PHB. Three parameter were studied to get the optimum value for the production of PHB there are fermentation temperature, agitation speed and the volume of oil palm trunk sap. Fermentation was done in 500mL shake flask that containing mineral salt medium, OPTS and inoculums. The fermentation process were done at 48 hours with different levels of parameters. Then the product were analysed for cell dry weight and PHB content. Then, for the scale up analysis, 1.5L inoculums, 2L carbon source where the mixture of glucose, fructose and sucrose were the same as OPTS sugar composition, 2L of MSM and 10.5L of distilled water made 15L working volume. The fermentation were done for 72 hours and sampling every 6 hours. Based on the result of cell dry weight, the optimum temperature; agitation speed and volume of oil palm trunk sap were 32.6°C, 162.5 rpm and 38.8% while the highest predicted concentration of PHB and cell dry weight were 1.985 g/L and 1.401 g/L. The highest production of PHB and cell dry weight were at 72 hours for first run that are 0.419 g/L and 4.5 g/L respectively while in second run the highest production of PHB at 12 hour and 48 hours for cell dry weight that are 0.494 g/L and 4g/L respectively.